Novel Two-dimensional Nanomaterials and Their Gas Sensing Properties - (:unkn) unknown (My University, 2015)
Graphene, an atomic thin two-dimensional (2D) material with C atoms arranged in a honeycomb lattice, has sparked an unprecedented research interest across various scientific communities since its initial mechanical isolation in 2004. The linear energy dispersion with respect to the momentum within 1 eV around the Fermi level at the high symmetric K (Dirac) points in the Brillouin zone renders graphene a wonder material for scientists. However, graphene’s semimetallic nature significantly limits its high-end applications, e.g., in digital logic circuits. Therefore, continued efforts in opening the band gap for graphene and in searching for novel 2D semiconducting materials are rewarding. Various methods have been proposed for generating band gaps in graphene and other related 2D nanomaterials; however, few can be utilized to tune the band gap over a wide range on the same device and many are realized at the cost of severe degradation of carrier mobility. Recently, a new graphene-based crystalline structure, graphene monoxide (GMO), has been discovered based on electron diffraction observations during in situ thermal reduction of multilayer graphene oxide (GO) under vacuum in a transmission electron microscope (TEM) chamber. Supported by infrared spectroscopy and first-principles calculations, the new 2D material was identified as a two-phase hybrid containing GMO domains that evolve in the graphene matrix. GMO extends the electronic property of a graphene derivative into the semiconductor world, enabling potential applications for nanoelectronics. Another route to address the graphene band gap bottleneck is to search for new 2D nanomaterial candidates, among which 2D transition metal dichalcogenides (e.g., MoS2) and black phosphorus (BP) are attracting significant attention. Although both are layered structures and have a tunable band gap, a higher carrier mobility and a wider band gap ranging from 0.3 eV for bulk-like BP to 1.8 eV of monolayer BP make BP an outstanding candidate for future electronic applications. Conductance-based nanoscale gas sensors based on these 2D nanomaterials are attractive due to their superior sensitivity/selectivity and relatively low cost. Experimental studies have shown that in general semiconducting materials exhibit better sensitivity than insulating/metallic materials. Thus, it is crucial to understand the gas sensing mechanism of semiconducting materials and to gain better insights into the performance enhancement. This thesis aims to explore the fundamental properties of novel 2D nanomaterials and to understand their gas sensing performance. Various GMO properties were calculated using density functional theory (DFT)-based techniques. Infrared (IR) spectra of GMO were calculated for both pure GMO and GMO domains embedded into the graphene matrix to facilitate its identification during formation. GMO has three IR active modes that are distinctive from those of graphene and GO. The electronic and mechanical properties of GMO were predicted to illuminate its potential applications in semiconductor devices. The band gap of GMO can be tuned over a wide range from 0 to 1.35 eV. The capability of heat removal in intrinsic GMO was also simulated with and without planar lattice strains and compared with that of graphene and silicon. GMO exhibits a superior thermal conductivity (>3,000 Wm-1K-1), 80% of that of graphene along the armchair direction for large lateral sample sizes (>5 µm). The magnetic properties of zigzag graphene nanoribbons (ZGNRs) induced by GMO domains (or epoxy pair chains) were investigated. The epoxy pair chains can generate finite spin moments in ZGNRs irrespective of the spin coupling between ribbon edges. The gas sensing properties of selected 2D nanomaterials were characterized both theoretically and experimentally. First, we developed statistical thermodynamics models with the gas binding energy from DFT calculations as the only input to characterize the monolayer gas adsorption density on graphene and BP thin films. Our statistical thermodynamics models can successfully predict the gas adsorption density with high accuracy compared with experimental data. Second, an analytical model was established to interpret why semiconducting materials are preferred for gas sensing applications using a BP thin film-based gas sensors as an example. The sensitivity model suggests that the optimum thickness of BP thin film is from several to 10+ nm, corresponding with a band gap of 0.3 to 0.6 eV. Third, van der Pauw and Hall measurements were performed to obtain the sheet resistance, the carrier concentration, and the carrier mobility for thermally-reduced GO (TRGO) at various temperatures to illuminate relative contributions from the carrier concentration and the carrier mobility to the sheet resistance change upon gas adsorption, which suggests that the conductance change upon gas adsorption mainly results from the carrier concentration change. Finally, the sensitivity enhancement from the nanocrystalline particles deposited on the surface of graphene-base materials was also investigated.
Keywords: Black Phosphorus; First-Principles Calculations; Gas Sensors; Graphene Monoxide